2014
DOI: 10.1177/2048872614552057
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between the amplitude of Osborn wave and core body temperature

Abstract: The amplitude of the J wave in the admission ECG of hypothermic patients may not accurately predict the core body temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 63 publications
1
7
0
1
Order By: Relevance
“…It has been shown that the amplitude of the J-point is inversely proportional to the core temperature and is reversible by gradual rewarming [7,26]. This phenomenon fits with our results of higher prevalence in patients treated with 33°C.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…It has been shown that the amplitude of the J-point is inversely proportional to the core temperature and is reversible by gradual rewarming [7,26]. This phenomenon fits with our results of higher prevalence in patients treated with 33°C.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…W opisanych dotychczas przypadkach analizowano korelację amplitudy fali J i temperatury ciała [7], liczbę odprowadzeń, w których obserwowano falę [2], a także związek z zaburzeniami równowagi kwasowo-zasadowej i wymiany gazowej [4] oraz arytmiami komorowymi [5]. Pojedyncze doniesienia nie pozwoliły jednak na stwierdzenie istotnych zależności.…”
Section: Dyskusjaunclassified
“…Normal body temperature is defined as 35.5-37.5 • C in healthy volunteers, although different ranges have been described depending on the site where the body temperature is measured. 1 Body temperature values outside the normal range have been reported to result in substantial changes to the surface electrocardiographs (ECGs), such as heart rate, [2][3][4][5] QRS duration, [4][5][6][7] J-wave prevalence, 4,[8][9][10][11][12] and QT interval duration. 4,6,[13][14][15] Even within the normal range, body temperature has been reported to have an effect on the corrected QT interval (QTc interval).…”
Section: Introductionmentioning
confidence: 99%